A COMPARISON BETWEEN POSTOPERATIVE TROPONIN ELEVATION IN AN OFF-PUMP VERSUS CONVENTIONAL CORONARY ARTERY BYPASS GRAFT IN PREDICTING THE SHORT-TERM OUTCOME - AHMED, MARYAM RAMADHAN; BAHJET, ALAA SALIM (Journal of Duhok University, 2023)
Background: Although, advancements in techniques and perioperative management in coronary artery bypass surgery the elevation of postoperative troponin still occurs commonly. In this regard, we aimed to assess the degree of myocardial injury by measuring and comparing the levels of cardiac troponin I in the postoperative period of conventional versus off-pump coronary artery bypass graft and identify the most associated factors. Patients and methods: This prospective cohort study included the patients who underwent conventional coronary artery bypass surgery (46 patients) and off-pump coronary artery bypass surgery (34 patients), at Azadi heart Center in Duhok province during the period between 25th November 2021 and 25th May 2022. Results: The total amount of cardiac troponin release was significantly higher in the conventional than in the off-pump group. At one hour, the conventional means was 7.13 ng/ml while the off-pump was 1.56 ng/ml, p < 0.0001and at 24 hours, the convention mean was 5.51 ng/ml while the off-pump was 1.24 ng/ml, p < 0.001. The most associated factors in the conventional compared to the off-pump were advanced age, male gender, hypertension, renal impairment, Previous myocardial infarction, and timing of surgery. the main independent factors associated with cardiac troponin I elevation within 24 hours following conventional coronary artery bypass surgery were overweight, chronic renal failure, Smoking, and urgent procedure status. Conclusion: This study showed that the patients who underwent the conventional group had significantly higher levels of troponin I at 1 hour and 24 hrs, postoperatively. The higher postoperative troponin I among patients who underwent the conventional group was associated with being overweight, smoking, having chronic renal failure, and using urgent procedure status